Never give up : my life in the wild - Grylls, Bear (National Geographic, 2022)
The global adventurer provides insight into what it's really like to explore places where few would dare to go and discusses the valuable lessons he's learned in the wild, sharing his most personal challenges and achievements and celebrating the true value of adventure.